2013
DOI: 10.1063/1.4849015
|View full text |Cite
|
Sign up to set email alerts
|

Local environment of silicon in cubic boron nitride

Abstract: Articles you may be interested inHigh quality single atomic layer deposition of hexagonal boron nitride on single crystalline Rh (111) four-inch wafers Rev. Sci. Instrum. 85, 035101 (2014); 10.1063/1.4866648Identification of B-K near edge x-ray absorption fine structure peaks of boron nitride thin films prepared by sputtering deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…We recently showed thatDFT can reproduce theXANES of crystalline cBN [39] and hBN [40], and identified substitutional O defects in electron irradiated cBN [41]. Calculations of XANES have successfully reproduced experimental defect signatures for Si incorporated in cBN [42], distinguished between tri-and quad-coordinated Si in graphene [43], identified the local environment of ion implanted B or N in graphene [44], and reproduced the spectra of various dangling bond arrangements on the edge of a graphene sheet [45,46]. Recent work has also revealed signatures in experiment and in calculations resulting from B-terminated tetravacancies in monolayer hBN [47].…”
Section: Introductionmentioning
confidence: 89%
“…We recently showed thatDFT can reproduce theXANES of crystalline cBN [39] and hBN [40], and identified substitutional O defects in electron irradiated cBN [41]. Calculations of XANES have successfully reproduced experimental defect signatures for Si incorporated in cBN [42], distinguished between tri-and quad-coordinated Si in graphene [43], identified the local environment of ion implanted B or N in graphene [44], and reproduced the spectra of various dangling bond arrangements on the edge of a graphene sheet [45,46]. Recent work has also revealed signatures in experiment and in calculations resulting from B-terminated tetravacancies in monolayer hBN [47].…”
Section: Introductionmentioning
confidence: 89%
“…[15,[42][43][44][45][46][47] Using DFT methods, Liu et al [47] revealed that the Si impurity prefers the B site, but as opposed to C, it severely deforms the h-BN structure preserving the sp 3 -like bonding.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Majety et al [45] reported a deep donor level of about 1.20 eV using the same technique and concluded that Si-doped h-BN is not suitable for room temperature device applications. Inspired by the experimental realization of Si-doped h-BN monolayers, [44,45] a systematic study of the physical properties of various possible Si atomic configurations will be interesting. Also, the knowledge of the dependence of physical properties for a Si-doped h-BN monolayer on the defect charge states is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…5 Further attempts on the effective doping of these lms towards p-and n-type conductivity have been made including ion implantation and in situ doping respectively. [14][15][16][17][18] However, doping of epitaxial c-BN lms has been rarely presented. 8 However, ion energies and radiation doses during the implantation process need to be precisely controlled because the defects are inevitably accompanied by radiation damage, which will probably lead to the eventual destruction of the c-BN cubic phase and to a transformation into a mechanically so hexagonal BN (h-BN) phase.…”
Section: Introductionmentioning
confidence: 99%